2023
DOI: 10.1002/tox.23730
|View full text |Cite
|
Sign up to set email alerts
|

Matrine restrains the development of colorectal cancer through regulating the AGRN/Wnt/β‐catenin pathway

Abstract: Background Colorectal cancer is a common malignant digestive tract tumor. This study aimed to explore the biological role and potential underlying mechanism of matrine in colorectal cancer. Methods The mRNA expression of AGRN was measured using RT‐qPCR. Cell proliferation, migration, invasion and apoptosis were determined using CCK‐8, EdU, transwell assays and flow cytometry, respectively. Xenograft tumor experiment was performed to explore the action of matrine and AGRN on tumor growth in colorectal cancer in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…Concerning new findings not yet clearly linked to HNSCC, some authors found that AGRN downregulation reduces cell proliferation, migration, invasion, and enhances apoptosis in colorectal cancer cells. Of note, they observed also that matrine, an alkaloid found in plants, has anti-tumor effects on colorectal cancer cells by inactivating the Wnt/ -catenin pathway via regulating AGRN expression [ 75 ]. Hence, AGRN could represent a potential target for therapies also in HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning new findings not yet clearly linked to HNSCC, some authors found that AGRN downregulation reduces cell proliferation, migration, invasion, and enhances apoptosis in colorectal cancer cells. Of note, they observed also that matrine, an alkaloid found in plants, has anti-tumor effects on colorectal cancer cells by inactivating the Wnt/ -catenin pathway via regulating AGRN expression [ 75 ]. Hence, AGRN could represent a potential target for therapies also in HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…21 There exists a substantial body of research demonstrating the antitumor properties of matrine, which has led to its extensive utilization in clinical tumor therapy. 22,23 For example, this drug has been used to treat liver, stomach, prostate, breast, colon, lung, and other cancers. [24][25][26][27][28][29] In addition, it has therapeutic effects on Alzheimer's disease, encephalomyelitis, asthma, myocardial ischemia, RA, osteoporosis, and other diseases.…”
Section: Matrinementioning
confidence: 99%
“…There exists a substantial body of research demonstrating the antitumor properties of matrine, which has led to its extensive utilization in clinical tumor therapy 22,23 . For example, this drug has been used to treat liver, stomach, prostate, breast, colon, lung, and other cancers 24–29 .…”
Section: Matrinementioning
confidence: 99%
“…Matrine is a kind of alkaloid, which is mainly isolated from Sophora flavescens (Li et al, 2023). At present, a large number of studies have confirmed that matrine has an anti-tumor effect, which can inhibit tumor cell proliferation, block cell cycle, induce apoptosis, inhibit tumor cell metastasis, and so on (Chen et al, 2022).…”
Section: Introductionmentioning
confidence: 99%